A study of the relationship between apo E genotypes and transitions of HDL subfractions in uncomplicated diabetes mellitus type 2, and the effect of various anticoagulants on lipoprotein levels. - Rashid, Faridah Abdul (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
A total of 114 type 2 diabetic subjects who attended the Diabetes Clinic in Hospital USM were selected for this study. Fasting venous blood was obtained from each patient and was analysed. The Chemical Pathology Laboratory performed Lipid Profile including Total Cholesterol (TC), Triglycerides (:G), LD~ Cholesterol. (LD~C), an~ HDL Cholesterol (HDLC). The Endocrinology Laboratory perfonned Diabetes Profile Including Fasting Plasma Glucose ((FPG) and hemoglobin AlC (A1C). More than two thirds (71 %) subjects had hig~ TC (~ ?·2 mmol/L); 90% had high LDLC (~ 2.6 mmol/L; 81% had low HDLC (< 1.55 mmol/L); and 42Yo had high TG (~ 1.71 mmol/L). The most common pattern of ~yslipidaemia ~as mixed hyperl.ipidaemia (37%),. ~allowed ?Y .hyperch?lesterolemia (34%) and hypertriglyceridaemia (5%). Glycaemic control and ethnictty were significantly Important determinants of elevated TC, LDLC, and TG. Gender influenced TC. Body Mass Index (BMI) influenced TG. The conclusion of.this study i~ tha~ hyperlipidae~ia is prevalent, es~e~ially h~ercholesterolaemia, and is a major problem In ~e 2 diabetics. Gly~a~mtc con~ol and .ethntcity were Important determinants of diabetic dyslipidaemia. Age, gender, ethntctty, duration of diabetes, BMI, smoking, family history of diabetes, dan AlC do not affect HDLC.